Data Integrity Verification Using MPT (Merkle Patricia Tree) in Cloud Computing - Mathiyalahan, Subasri; Manivannan, Shobana; Nagasundaram, Mahalakshmi; Ezhilarasie, R (International Journal of Engineering and Technology, 2018)
Data integrity of outsourced data is main problem in CSP (cloud service provider). Space overhead and computation complexity are very high issue in recent PDP(Provable Data Possession) verification schemes. To overcome such issues MPDP (Mobile Provable Data Possession) schemes using hash tree data structure and Boneh-Lynn-Snacham short signature scheme have been used over decade. Data dynamics is well supported in MPDP scheme via block less verification, dynamic data operations, stateless verification, and verification out sourcing. But still there are some operations which can be performed much more efficiently in some other way than that of the two methods prescribed above. Operations in particular, data modification operations like insertion and deletion operations is somewhat difficult or in other words time consuming in hash tree data structure. In this paper, we have deployed an improved hash tree structure called MPT (Merkle Patricia Tree) for integrity checking.MPT is combination of MHT (Merkle Hash Tree) and patricia tree where each node consists of key-value pairs.Â As of now, MPT has been used only in block chain technology for providing authentication of transactions through Ethereum. Â